Study of use of non-invasive ventilation in patients of acute exacerbation of chronic obstructive pulmonary disease - Joshi, Vrunda; Nyrvan Baishya,; Sangramsingh Dixit,; Athavale AU, (Asian Journal of Medical Sciences, 2022)
Background: Chronic obstructive pulmonary disease (COPD) is one of the common causes of morbidity as well as mortality particularly in developing countries including India. Acute exacerbations of COPD remain one of the common causes of intensive care unit admissions worldwide and respiratory failure remains one of the common life-threatening complications of such an acute exacerbation. In patients with respiratory failure invasive as well as non-invasive ventilation (NIV) may be used. Many studies have shown that NIV is effective in managing these patients with an advantage over invasive ventilation which may associated with complications associated with endotracheal intubation. Aims and Objectives: (i) To assess the effectiveness of NIV in patients coming with type 2 respiratory failure. (ii) To find out the duration of NIV required for clinical improvement with the end point being normalization of arterial pH. Materials and Methods: This was an observational and retrospective study conducted in the Department of Pulmonary Medicine Seth GS Medical College and KEM Hospital, Mumbai. The duration of study was 2 years. Forty-four patients of acute exacerbation of chronic obstructive airway disease were included in this study on the basis of a predefined inclusion and exclusion criteria. The computerized record of all the patients who had been given NIV for acute exacerbations of chronic airway disease was analyzed. The data analysis included comparing the arterial blood gas pH and the use of NIV. The improvement in the pH value was correlated with the use of NIV. Other comorbidities were included in the data and correlated with the pH values. Results: In our study, the most of the patients belonged to the age group of 51–60 years (31.8%) followed by 41–50 years (29.5%) and 61–70 years (20.5%). Improvement in pH was observed in 42 out of 43 studied cases. It was observed that the average number of hours of NIV per patient was 10–15 h (20.5%) followed by 16–20 h (15.9%) of the study population. Conclusion: NIV is safe and effective form of managing patients of acute exacerbation of chronic obstructive airway disease.